View-based textual modelling - Goldschmidt, Thomas (KIT Scientific Publishing, 2011)
This work introduces the FURCAS approach, a framework for view-based textual modelling. FURCAS includes means that allow software language engineers to define partial and overlapping textual modelling languages. Furthermore, FURCAS provides an incremental update approach that enables modellers to work with multiple views on the same underlying model. The approach is validated against a set of formal requirements, as well as several industrial case studies showing its practical applicability.
English
Keywords: Textual Modelling; Model-Driven Engineering; View-Based Modelling; Domain Specific Languages